2019
DOI: 10.1080/01635581.2019.1595053
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Serum Biomarkers of Inflammation and Quality of Life in Clinically Stable Women with Estrogen Receptor Positive Metastatic Breast Cancer

Abstract: Title: Body composition, serum biomarkers of inflammation and quality of life in clinically stable women with estrogen receptor positive (ER+) metastatic breast cancer (BC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…In both groups, lipid infiltration was below the threshold (< 37.8 HU) raising the need to measure both the sarcopenia indicator and the muscle quality indicator, both of which are correlated with an increased risk of death [ 9 ]. Using a threshold for SMI of ≤ 41cm 2 /m 2 as proposed by Martin et al, another cross-sectional study in 41 metastatic breast cancer patients reported a 34% prevalence of sarcopenia [ 64 , 65 ]. These results reinforce the need to systematically assess body composition and sarcopenia in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, lipid infiltration was below the threshold (< 37.8 HU) raising the need to measure both the sarcopenia indicator and the muscle quality indicator, both of which are correlated with an increased risk of death [ 9 ]. Using a threshold for SMI of ≤ 41cm 2 /m 2 as proposed by Martin et al, another cross-sectional study in 41 metastatic breast cancer patients reported a 34% prevalence of sarcopenia [ 64 , 65 ]. These results reinforce the need to systematically assess body composition and sarcopenia in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a correlation between sarcopenia and long-term prognosis in metastatic colorectal cancer and metastatic breast cancer. 13,24 Furthermore, Ataseven et al reported on the utility of the skeletal muscle index measured through CT as a prognostic predictor in advanced ovarian cancer. 25 However, no study has shown a correlation between sarcopenia and prognosis in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that PMI is an independent prognostic factor among patients with organ metastatic cervical cancer. Recent studies have reported a correlation between sarcopenia and long‐term prognosis in metastatic colorectal cancer and metastatic breast cancer 13,24 . Furthermore, Ataseven et al reported on the utility of the skeletal muscle index measured through CT as a prognostic predictor in advanced ovarian cancer 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of a retrospective study showed that breast WAT inflammation is usually generated in overweight/obese BC women and may be related to abnormal circulatory indicators related to metabolic syndrome ( 81 ). Previous studies have confirmed the systemically BC promotion effect of adipose inflammation via circulating pro-inflammatory cytokines, such as IL-6 and TNF-α ( 82 ). Since BC is located in a fat-rich environment, recent studies have mainly focused on the local effects of inflamed adipose tissue, including the impact of cytokine levels in mammary adipose tissue on BC ( 83 ).…”
Section: Mechanisms Linking Obesity and Breast Cancermentioning
confidence: 70%